Virtual Interpolation Images of Tumor Development and Growth on Breast Ultrasound Image Synthesis With Deep Convolutional Generative Adversarial Networks. (27th June 2020) - Fujioka, Tomoyuki; Kubota, Kazunori; Mori, Mio; Katsuta, Leona; Kikuchi, Yuka; Kimura, Koichiro; Kimura, Mizuki; Adachi, Mio; Oda, Goshi; Nakagawa, Tsuyoshi; Kitazume, Yoshio; Tateishi, Ukihide
Abstract : Objectives: We sought to generate realistic synthetic breast ultrasound images and express virtual interpolation images of tumors using a deep convolutional generative adversarial network (DCGAN). Methods: After retrospective selection of breast ultrasound images of 528 benign masses, 529 malignant masses, and 583 normal breasts, 20 synthesized images of each were generated by the DCGAN. Fifteen virtual interpolation images of tumors were generated by changing the value of the input vector. A total of 60 synthesized images and 20 virtual interpolation images were evaluated by 2 readers, who scored them on a 5‐point scale (1, very good; to 5, very poor) and then answered whether the synthesized image was benign, malignant, or normal. Results: The mean score of overall quality for synthesized images was 3.05, and that of the reality of virtual interpolation images was 2.53. The readers classified the generated images with a correct answer rate of 92.5%. Conclusions: A DCGAN can generate high‐quality synthetic breast ultrasound images of each pathologic tissue and has the potential to create realistic virtual interpolation images of tumor development.